(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The incidence of sarcopenia continues to increase with age. The prevalence ranges from 5-13 percent in those aged 60-70 years and 11-50 percent in those aged >80 years. Decreased walking speed is one of the factors that can affect the status of weakness in the elderly. The purpose of the study was to analyze the intake of vitamin D and the duration of exposure to the sun with the walking speed of the elderly. The research design was cross sectional, at Panti Bhakti Kasih Siti Anna, Pangkalpinang City, 2020. The research sample was 22 of elderly. The results of the study stated that 68.2 percent of respondents were women with an average age of 80 years. The category of obesity (36.4%) and slow walking speed (95.5%) were the dominant results. The average daily intake of vitamin D in the elderly is 241.8 IU with 30 minutes of sun exposure. Statistical analysis stated that there was a relationship between vitamin D intake and duration of sun exposure with the walking speed of the elderly (p